PENGARUH WORK-FAMILY CONFLICT TERHADAP PERKEMBANGAN KARIR PEGAWAI PEREMPUAN DI LAPAS PEREMPUAN KELAS IIA JAKARTA - Praningtyas, Azzahra Dinda; Rahayu, Mulyani (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The existence of women is often ignored in social and state life, the stigma of women only having obligations and responsibilities as housewives is still felt today. The dual role of career women who work can sometimes cause conflict at work or in the family sphere. This work-family entanglement also occurs among female employees in Jakarta Women's Correctional Institution, which impacts the career development of these female employees. The purpose of this research is to find out and examine the influence of work-family conflict on the career development of female employees in Jakarta Women's Correctional Institution. The total population studied was 71 female employees. The method used in this research is quantitative with a total sampling technique. The result obtained by this research through the regression equation shows that there is an influence of work-family conflict on the career development of female employees in the Jakarta Women's Correctional Institution. Keywords: Work-Family Conflict; Career Development; Correctional Institution